(untitled) - Babadjanov, B.D.; Matmurotov, K.J.; Otajonov, J.H. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the effectiveness of minimally invasive endovascular methods in the treatment of diabetic gangrene of the lower extremities, depending on the risk of loss of the limb. Material and methods: the results of inpatient treatment of 323 patients (225 (69.6%) men and 98 (30.4%) women) with surgical complications of diabetic foot syndrome who were in 2012-2018 were analyzed. at the Republican Center for purulent surgery and surgical complications of diabetes mellitus at the 2nd TMA clinic. All patients suffered from type 2 diabetes. 203 patients were given insulin to correct their blood sugar levels. The neuroischemic form of diabetic foot syndrome was diagnosed in 271 (83.9%) patients, ischemic - in 52 (16.1%) patients. Results: large ulcerative defects (W3) were observed in 123 (38.1%) patients, an average degree (W2) of the wound process occurred in 136 (42.1%), a superficial wound defect (W1) in 43 (13.3%). Severe ischemia (I3) of the limb was diagnosed in 76 (23.5%) patients, moderate ischemia (I2) in 135 (41.8%), and light ischemia in 112 (34.6%). Conclusions: long-term intraarterial catheter therapy in patients with diabetic gangrene of the lower limb with a high risk of it after complete balloon angioplasty increases the chance of maintaining the limb support function up to 88.7%. The use of a complex of minimally invasive X-ray endovascular methods for treating lower extremity diabetic gangrene, even in patients with a high risk of limb loss (77-94% wifi), can reduce the frequency of hip amputation from 12.6 to 8.0% and reduce mortality from 5.7 to 3, 2%.